Face Synthesis - Liu, Zicheng; Guo, Baining (Handbook of Face Recognition, 2004)
How to synthesize photorealistic images of human faces has been a fascinating yet difficult problem in computer graphics. Here, the term “face synthesis” refers to synthesis of still images as well as synthesis of facial animations. In this chapter, we focus more on the synthesis of still images and skip most of the aspects that mainly involve the motion over time. We review recent advances on face synthesis including 3D face modeling, face relighting, and facial expression synthesis.